Social sector expenditures in the 1990s: analysis of central and state budgets - Dev, S. Mahendra; Moou, Jos (2002)
This paper focuses on social sector expenditure in the 1990s, and looks at several aspects, including overall levels of allocation, expenditure on health and education and interstate disparities. India's social sector expenditure in the 1990s was lower than that in the 1980s and also less than that of most other developing countries. With India ranking 115th in the Human Development Index, there is an obvious need to step up social sector expenditure and improve fund utilisation. - Reproduced.
Keywords: Budget